The Growth of the Population’s Employment and Social Progress - Sardorbek Usmonxudjaevich Abdullayev (Genius Journals, 2022)
The article presents the relationship between the growth of the population’s employment and social progress. Also, types, kinds and levels of the employment of population are considered in this article.
Keywords: Employment; living standard; abour marke; wages